2022
DOI: 10.1177/10105395221115220
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Loneliness, Peer, and Parental Relationship With Smoking: A Cross-Sectional Analysis of Adolescents Across South-East Asia

Abstract: Tobacco use among youth in the South-East Asian region is quite prevalent. This study aims to examine if psychosocial factors (perceived loneliness, peer, and parental relationships) were associated with adolescent smoking, and whether the effects were different according to sex and age. Data came from the Global School-based Student Health Surveys collected between 2012 and 2015 in Brunei, Cambodia, Indonesia, Laos, Malaysia, Philippines, Thailand, Timor-Leste, and Vietnam. 64 578 (males = 48.5%) adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…There is substantial evidence for the impact of loneliness on substance use in adolescents. Adolescents who felt lonely were at 1.75, 1.80, and 1.55 times higher risk of smoking [ 22 ], alcohol consumption [ 9 ], and habitual drug use [ 8 ], respectively, than those who felt less lonely. A study by Ingram et al [ 4 ] showed that participants relied on substance use because they had no other way of escaping periods of loneliness or loneliness-related pain.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence for the impact of loneliness on substance use in adolescents. Adolescents who felt lonely were at 1.75, 1.80, and 1.55 times higher risk of smoking [ 22 ], alcohol consumption [ 9 ], and habitual drug use [ 8 ], respectively, than those who felt less lonely. A study by Ingram et al [ 4 ] showed that participants relied on substance use because they had no other way of escaping periods of loneliness or loneliness-related pain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, smoking reduces hunger, which makes more women continue to smoke to control their weight [ 36 ]. Also being in a social environment that is more susceptible to anxiety and depression is a barrier to quitting [ 37 ]. A study in China found that in 1990, the focus of female tobacco control was passive smoking, but in 2017, smoking and passive smoking became equally crucial for female tobacco control [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the present data, loneliness affects people’s behavior, specifically behaviors that may be involved in the deterioration of physical health, such as smoking, drinking, lack of physical activity, and increased body weight. There is evidence that loneliness is associated with smoking or lower possibilities of quitting smoking, especially when loneliness co-exists with self-reported emotional problems [ 13 ], while lack of close friends and loneliness have also been related to smoking [ 49 ]. Studying behavioral risk factors is also challenging, although their separate effects on chronic disease occurrence [ 23 , 50 ] and all-cause mortality [ 51 ] are already known.…”
Section: Discussionmentioning
confidence: 99%